Understanding a digital tool for the continuous economic valuation of critical raw materials mining projects - Islam, M. A.; Barakos, George; Mischo, H. (AusIMM, 2024)
The strategic sectors of decarbonisation, digitalisation, aerospace and defence heavily depend on a secure supply of critical raw materials worldwide. However, several well-known critical raw materials mining projects had to close due to unforeseen costs that resulted in economic instability stemming from a misinterpretation of the features of the orebody and other boundary conditions. In addition to uncertainties with mineral prices, such misinterpretations are related to ground conditions, metallurgical recoveries, and geological consistency. Circumstances occur with unexpected discontinuities, differentiated geotechnical and rock mechanic properties of orebodies, overly optimistic recoveries, and payable products during the operation. Using digital technologies in mining operations has demonstrated advantages in reduced labour and wear component costs and higher production. Nevertheless, the application of artificial intelligence, machine learning, data analytics, predictive analytics, real-time data, and other relevant digital technologies in mine planning and optimisation still needs to be explored. An in-depth study is required to reveal the potential of digital technology applications in mining planning and research domains. This study aims to present the current application of digital technologies in mine planning and operation and the extent to which such technologies can potentially handle the evaluation and prediction of techno-economic uncertainties during the project evaluation and implementation. Moreover, the study seeks to integrate the findings and define frameworks of a digital tool for the continuous economic analysis of critical raw material projects from the resource evaluation stage through project completion. Text-mining algorithms supported by Python programming are utilised to study insight reports from leading software companies and consulting organisations and relevant published papers in international peer-reviewed journals and conference proceedings. More funding and the interest of academics and software developers would be drawn in if the potential applications of digital technology in raw material sectors are made more apparent.